Eastern Orthodox Christianity : a western perspective - Clendenin, Daniel B. (Grand Rapids, MI : Baker Academic, 2003)
"In this survey, Daniel Clendenin introduces Protestants to Eastern Orthodox history and theology with the hope that the two groups will come to see their traditions as complementary and learn to approach one another with a "hermeneutic of love" that fosters "mutual respect, toleration, and even support.""--BOOK JACKET.
1. On Smells and Bells: An Apologia for Orthodoxy -- 2. The Forgotten Family: A Brief History -- 3. The Mystery of God: Apophatic Vision -- 4. The Image of Christ: Theology in Color -- 5. The Witness of the Spirit: Scripture and Tradition -- 6. The Deification of Humanity: Theosis -- 7. A Hermeneutic of Love -- Epilogue: Orthodox-Evangelical Dialogue: Past, Present, and Future.
Includes bibliographical references and index.
Keywords: Orthodox Eastern Church -- Doctrines